Proteomic Investigation into Betulinic Acid-Induced Apoptosis of Human Cervical Cancer HeLa Cells - Xu, Tao; Pang, Qiuying; Zhou, Dong; Zhang, Aiqin; Luo, Shaman; Wang, Yang; Yan, Xiufeng (PLOS ONE, 2014)
Betulinic acid is a pentacyclic triterpenoid that exhibits anticancer functions in human cancer cells. This study provides evidence that betulinic acid is highly effective against the human cervical cancer cell line HeLa by inducing dose- and time-dependent apoptosis. The apoptotic process was further investigated using a proteomics approach to reveal protein expression changes in HeLa cells following betulinic acid treatment. Proteomic analysis revealed that there were six up- and thirty down-regulated proteins in betulinic acid-induced HeLa cells, and these proteins were then subjected to functional pathway analysis using multiple analysis software. UDP-glucose 6-dehydrogenase, 6-phosphogluconate dehydrogenase decarboxylating, chain A Horf6-a novel human peroxidase enzyme that involved in redox process, was found to be down-regulated during the apoptosis process of the oxidative stress response pathway. Consistent with our results at the protein level, an increase in intracellular reactive oxygen species was observed in betulinic acid-treated cells. The proteins glucose-regulated protein and cargo-selection protein TIP47, which are involved in the endoplasmic reticulum pathway, were up-regulated by betulinic acid treatment. Meanwhile, 14-3-3 family proteins, including 14-3-3β and 14-3-3ε, were down-regulated in response to betulinic acid treatment, which is consistent with the decrease in expression of the target genes 14-3-3β and 14-3-3ε. Furthermore, it was found that the antiapoptotic bcl-2 gene was down-regulated while the proapoptotic bax gene was up-regulated after betulinic acid treatment in HeLa cells. These results suggest that betulinic acid induces apoptosis of HeLa cells by triggering both the endoplasmic reticulum pathway and the ROS-mediated mitochondrial pathway.